Toxic effects of chrysoidine on human serum albumin: isothermal titration calorimetry and spectroscopic investigations. (14th July 2015) - Sun, Haoyu; Liu, Yingxue; Li, Meng; Han, Songlin; Yang, Xudan; Liu, Rutao
Abstract: Chrysoidine is widely used in industry as a type of azo dye, and is sometimes used illegally as a food additive despite its potential toxicity. Human serum albumin (HSA) is one of the most important proteins in blood plasma and possesses major physiological functions. In the present study, the conformational and functional effects of chrysoidine on HSA were investigated by isothermal titration calorimetry (ITC), multiple spectroscopic methods, a molecular docking study and an esterase activity assay. Based on the ITC results, the binding stoichiometry of chrysoidine to HSA was estimated to be 1.5:1, and was a spontaneous process via a single hydrogen bond. The binding of chrysoidine to HSA induced dynamic quenching in fluorescence, and changes in secondary structure and in the microenvironment of the Trp‐214 residue. In addition, the hydrogen bond (1.80 Å) formed between the chrysoidine molecule and the Gln‐211 residue. The esterase activity of HSA decreased following the addition chrysoidine due to the change in protein structure. This study details the direct interaction between chrysoidine and HSA at the molecular level and the mechanism for toxicity as a result of the functional changes induced by HSA structural variation upon binding to chrysoidine in vitro . This study provides useful information towards detailing the transportation mechanism and toxicity of chrysoidine in vivo . Copyright © 2015 John Wiley & Sons, Ltd.